1999
DOI: 10.1023/a:1018733420467
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Brain areas activated in human male sexual behavior have not been characterized precisely. For the first time, positron emission tomography (PET) was used to identify the brain areas activated in healthy males experiencing visually evoked sexual arousal. Eight male subjects underwent six measurements of regional brain activity following the administration of [15O]H2O as they viewed three categories of film clips: sexually explicit clips, emotionally neutral control clips, and humorous control clips inducing po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(90 citation statements)
references
References 40 publications
6
83
0
1
Order By: Relevance
“…For example, erotic stimuli elicit neuronal activities in brain areas commonly associated with the human reward system (e.g., Ishai, 2007;Karama et al, 2002;Mouras et al, 2003;Ponseti et al, 2006;Redouté et al, 2000;Safron et al, 2007;Stoléru et al, 1999). Visual stimuli of sexually attractive targets may also trigger schematic processes (e.g., evaluative, comparative, or associative processes, episodic memories, fantasizing).…”
Section: Stimulus-specific Processesmentioning
confidence: 99%
“…For example, erotic stimuli elicit neuronal activities in brain areas commonly associated with the human reward system (e.g., Ishai, 2007;Karama et al, 2002;Mouras et al, 2003;Ponseti et al, 2006;Redouté et al, 2000;Safron et al, 2007;Stoléru et al, 1999). Visual stimuli of sexually attractive targets may also trigger schematic processes (e.g., evaluative, comparative, or associative processes, episodic memories, fantasizing).…”
Section: Stimulus-specific Processesmentioning
confidence: 99%
“…This hypothesis is corroborated by neurophysiological evidence. Watching sexually attractive stimuli elicits neuronal activities in brain areas commonly associated with the human reward system (e.g., Ishai, 2007;Karama et al, 2002;Mouras et al, 2003;Ponseti et al, 2006;Redouté et al, 2000;Safron et al, 2007;Stoléru et al, 1999). Humans are assumed to be motivated by hedonism (e.g., Epstein, 1990) in that they try to reach and maintain positive affective states.…”
Section: Deliberate Delaymentioning
confidence: 99%
“…In a study of 6 patients with a history of psychogenic erectile dysfunction, it was shown that the inferior temporal regions on the right, superior prefrontal cortex and posterior parietal regions bilaterally, and the thalamus, were specifically activated upon sublingual administration of apomorphine [56]. In comparison, visually evoked sexual arousal (without drug treatment) was characterized by: bilateral activation of the inferior temporal cortex, a visual association area; activation of the right insula and right inferior frontal cortex, which are two paralimbic areas relating highly processed sensory information with motivational state, and activation of the left anterior cingulate cortex, another paralimbic area known to control autonomic and neuorendocrine functions [57]. More precise data are required to make a comparison in order to determine to which extent apomorphine activates brain structures which are kept silent in ‘drug–free’ sexual arousal.…”
Section: In Humansmentioning
confidence: 99%